Spatiotemporal effects of logging and fire on tall, wet temperate eucalypt forest birds - Lindenmayer, David B; Blanchard, Wade; Blair, David; Westgate, Martin J; Scheele, Ben C (Ecological applications, 2019)
Forests globally are subject to disturbances such as logging and fire that create complex temporal variation in spatial patterns of forest cover and stand age. However, investigations that quantify temporal changes in biodiversity in response to multiple forms of disturbance in space and time are relatively uncommon. Over a 10-yr period, we investigated the response of bird species to spatiotemporal changes in forest cover associated with logging and wildfire in the mountain ash (Eucalyptus regnans) forests of southeastern Australia. Specifically, we examined how bird occurrence changed with shifts in the proportion of area burned or logged in a 4.5 km radius surrounding our 88 long-term field survey sites, each measuring 1 ha in size. Overall species richness was greatest in older forest patches, but declined as the amount of fire around each site increased. At the individual species level, 31 of the 37 bird species we modeled exhibited a negative response to the amount of fire in the surrounding landscape, while one species responded positively to fire. Only nine species exhibited signs of recovery in the 6 yr of surveys following the fire. Five species were more likely to be detected as the proportion of logged forest surrounding a site increased, suggesting a possible "concentration effect" with displaced birds moving into unlogged areas following harvesting of adjacent areas. We also identified relationships between the coefficients of life history attributes and spatiotemporal changes in forest cover and stand age. Large-bodied birds and migratory species were associated with landscapes subject to large amounts of fire in 2009. There were associations between old growth stands and small-bodied bird species and species that were not insectivores. Our study shows that birds in mountain ash forests are strongly associated with old growth stands and exhibit complex, time-dependent, and species-specific responses to landscape disturbance. Despite logging and fire both being high-severity perturbations, no bird species exhibited similar responses to fire and logging in the landscape surrounding our sites. Thus, species responses to one kind of landscape-scale disturbance are not readily predictable based on an understanding of the responses to another kind of (albeit superficially similar) disturbance.